Functional and cognitive decline in older delirious adults after an emergency department visit. (7th September 2020) - Giroux, Marianne; Émond, Marcel; Nadeau, Alexandra; Boucher, Valérie; Carmichael, Pierre-Hugues; Voyer, Philippe; Pelletier, Mathieu; Gouin, Émilie; Daoust, Raoul; Berthelot, Simon; Lamontagne, Marie-Eve; Morin, Michèle; et al.
Abstract: Background: the aim of this study was to evaluate the impact of emergency department (ED) stay-associated delirium on older patient's functional and cognitive status at 60 days post ED visit. Methods: this study was part of the multi-centre prospective cohort INDEED study. This project took place between March 2015 and July 2016 in five participating EDs across the province of Quebec. Independent non-delirious patients aged ≥65, with an ED stay ≥8 hours, were monitored for delirium until 24 hours post ward admission. A 60-day follow-up phone assessment was conducted. Participants were screened for delirium using the Confusion Assessment Method. Functional and cognitive statuses were assessed at baseline and at the 60-day follow-up using OARS and TICS-m. Results: a total of 608 patients were recruited, 393 of which completed the 60-day follow-up. The Confusion Assessment Method was positive in 69 patients (11.8%) during ED stay or within the first 24 hours following ward admission. At 60 days, delirium patients experienced an adjusted loss of −2.9/28 [95%CI: −3.9, −2.0] points on the OARS scale compared to non-delirious patients who lost −1.6 [95%CI: −1.9, −1.3] ( P  = 0.006). A significant adjusted difference in cognitive function was also noted at 60 days, as TICS-m scores in delirious patients decreased by −1.6 [95%CI: −3.5, 0.2] compared to non-delirious patients, who showed a minor improvement of 0.5 [95%CI: −0.1, 1.1] ( P  = 0.03). Conclusion: seniors who developed ED stay-associated delirium have lower baseline functional and cognitive status than non-delirious patients, and they will experience a more significant decline at 60 days post ED visit.